Clinical Practice Guidelines for Auricular Fibrillation. - Lázaro De la Cruz Avilés; Félix Rolando Jorrín Román; Francisco De Jesús Valladares Carvajal; Pablo Rodríguez Díaz (Medisur)
Clinical Practice Guidelines for Auricular Fibrillation. This is the most common cardiac arrhythmia and can bring about deleterious consequences on the cardiac function and risk of systemic embolism. It includes important aspects as aetiology and trigger aspects, diagnosis, classification and treatment with emphasis on therapeutic emergencies. It includes assessment guidelines focused on the most important aspects to be accomplished.